Characterization of Clinical and Histological Rejection of Male Genital Tissues Using a Novel Microsurgical Rat Penile Transplantation Model. Issue 11 (November 2019) - Fidder, Samuel A.J.; Furtmüller, Georg J.; Simons, Brian; Oh, Byoung Chol; Chicco, Maria; Etra, Joanna W.; Brayton, Cory; Cooney, Carisa M.; Vasilic, Dalibor; Kern, Barbara; Lough, Denver; Lee, WP Andrew; et al.
Abstract : Background: Penis transplantation represents an exciting new avenue for restoration of male urogenitalia. However, little is known about the specific immunological features of penile transplants, limiting their application in complex urogenital reconstruction. To properly study this emerging form of transplantation, adequate preclinical models are a necessity. The purpose of this study is to establish a clinical and histological rejection classification of urogenital tissue transplants using a new rat heterotopic penile transplant model that includes preputial skin. Methods: Syngeneic and allogeneic heterotopic penile transplantations were performed on Lewis and Brown Norway rats using a new model designed by our group. Grafts were clinically and histologically monitored at postoperative days (POD) 3–30. Results: Six syngeneic and 25 allogeneic transplants were performed. All syngeneic and tacrolimus-treated grafts survived until endpoint. Allogeneic graft rejection is shown to follow a 4-stage clinical progression with all untreated allografts developing epidermal sloughing at POD7 and full rejecting between POD14 and POD16. Histological samples were used to develop a specific 4-grade rejection classification analogous to the 2007 Banff Criteria for skin-containing allografts. Conclusions: Graft skin and urethral lining tissue are first rejection targets followed by tunica albuginea and corpora cavernosa in a distal to proximal pattern. We established a robust and reproducible murine model to study the immunobiology of male genital tissue in the context of transplantation and developed a novel 4-grade clinical and histological rejection scale based on graft skin and urethral lining as the main targets of rejection.